Use of smartphones in family relationships of university students of the Nacional del Altiplano University of Puno - Yolanda Pari Ccama (2019)
The excessive use of Smartphone in young people has caused deterioration in family relationships. The objective of the research was to determine the relationship of the use of the Smartphone with family relationships in university students. The hypothetical deductive method was applied, the research is of a correlational descriptive type, a non-probabilistic sample was used for the convenience of 96 students, the survey technique was applied and as a Likert type questionnaire with 36 items raised by variables, dimensions. and indicators. The results showed that there is a relationship between the use of the Smartphone with family relationships, evidencing the deterioration of the face-to-face interaction between parents and children, poor compliance with family functions of socialization, recreation and affection that young people lack and the communication styles they practice at home are mostly passive. We conclude that the use of Smartphone has a significant positive average relationship with family relationships in university students. The educational institutions and the family must regulate the proper use of the Smartphone in family spaces, avoiding the deterioration of family relationships.